Nonmetastatic osteosarcoma of the extremity. Neoadjuvant chemotherapy with methotrexate, cisplatin, doxorubicin and ifosfamide. An Italian Sarcoma Group study (ISG/OS-Oss). Issue 6 (November 2014) - Ferrari, Stefano; Meazza, Cristina; Palmerini, Emanuela; Tamburini, Angela; Fagioli, Franca; Cozza, Raffaele; Ferraresi, Virginia; Bisogno, Gianni; Mascarin, Maurizio; Cefalo, Graziella; Manfrini, Marco; Capanna, Rodolfo; et al.
Background: Based on the results of the ISG/OS-1 study, the MAP regimen (methotrexate [MTX], doxorubicin [ADM] and cisplatin [CDP] with the addition of ifosfamide [IFO] in poor-responder patients) was investigated in patients with nonmetastatic osteosarcoma of the extremity (ISG/OS-Oss study). Patients and methods: Compared with the ISG/OS-1 study (cumulative doses: ADM 420 mg/m 2, MTX 120 g/m 2, CDP 600 mg/m 2, IFO 30 g/m 2 ), the ISG/OS-Oss study reduced the number of MTX cycles from 10 to 5 (cumulative MTX dose: 60 g/m 2 ) in order to diminish treatment duration and toxicity. Results: From January 2007 to June 2011, 171 patients (median age 16 years, 60% males) were registered. The limb salvage rate was 94% and the good pathologic response rate 51% (these figures were 92% and 48%, respectively, in the ISG/OS-1 study). At a median follow-up of 39 months (range, 4–80), the 5-year overall survival rate was 80% (95% CI, 73%-87%) and the event-free survival was 50% (95% CI, 39%-59%). For comparison, the 5-year overall and event-free survival rates in ISG/OS-1 were 73% (95% CI, 65%-81%) and 64% (95% CI, 56%-73%), respectively. Conclusions: This study confirms that in nonmetastatic osteosarcoma of the extremity, conservative surgery in more than 90% and a good pathologic response rate of 50% can be expected with primary chemotherapy based on the MAP regimen. The response and resection rates in the ISG/OS-Oss study are in the same range as those of the previous study, whereas the event-free survival is lower than that previously achieved. Since the only difference between the two studies was the cumulative dose of postoperatively given MTX, our data support the importance of the cumulative dose of MTX in the MAP regimen.